Pendidikan Matematika - Apriyani, Nurwinda (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
This article is the result of a theoretical study of mathematics educators. Not limited to profit or loss, but to see the contribution of an educator who is a reflection of students. There are 8 irrational thinking patterns that affect individual emotions that need to be considered and the teaching skills possessed by educators can be seen from 9 indicators as 'educational tools'.